Exploring Ethical Decision-Making in Forensic Accounting: Professional Moral Agency amid Corporate Scandals - Ramandei, Pilipus; Faisal; Marjono; Putranto, Panji; Astuti, Dewi Saptantinah Puji (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
The growing complexity of corporate misconduct has placed forensic accountants in high-risk ethical environments, where professional objectivity is often tested by legal ambiguity, organizational pressure, and institutional interests. This study aims to explore how professional moral agency is exercised by forensic accountants in high-stakes investigations, particularly when ethical decision-making extends beyond formal codes toward personal integrity and moral reasoning. Using a qualitative interpretative phenomenological approach, data were gathered from in-depth interviews with twelve certified forensic accountants involved in cases of financial fraud, asset misappropriation, and governance failures. The findings reveal that professional moral agency is exercised through an ongoing negotiation between professional standards, internalized ethical values, and situational pragmatism. Key mechanisms that influence ethical conduct include the presence (or absence) of organizational ethical infrastructure, the strength of moral identity, and the perceived legitimacy of institutional authority. In cases of acute ethical conflict, participants often rely on moral intuition, boundary-setting behavior, or even voluntary disengagement from assignments that compromise their professional integrity. This study contributes to forensic accounting by highlighting the importance of moral agency and ethical resilience as foundational elements in sustaining professional integrity beyond regulatory compliance and technical expertise.